Analisis Pengaruh Ketidakpastian Global dan Perkembangan Keuangan terhadap Investasi Asing Langsung di Indonesia: Institut Pertanian Bogor - Noviyanti, Fuzi; Sugema, Iman; Irawan, Tony (IPB University, 2023)
The world is currently facing unprecedented uncertainty in social, political, and economic aspects, which continuously evolve every year owing to extraordinary events that impact countries worldwide. In contrast, The growth strategy of a country organizes must include Foreign Direct Investment (FDI), especially in Indonesia. The fluctuation in foreign investment in Indonesia indicates that foreign investors also consider growing global uncertainty alongside the development of Indonesia’s financial sector. This study examines the relationship between global uncertainty and financial development on FDI in Indonesia from 1997 to 2020 using the Autoregressive Distributed Lag (ARDL) method. The results indicate that global uncertainty significantly negatively impacts Indonesia’s FDI in the short and long terms. However, global economic policy uncertainty positively influences Indonesia’s FDI in the long term. This indicates that Indonesia has become an attractive alternative for foreign investors during global economic policy uncertainty. Regarding financial development, the amount of credit provided by the domestic banking sector to the private sector in Indonesia positively influences Indonesia’s FDI in both the short and long terms. This demonstrates that Indonesia’s financial condition and infrastructure can determine foreign investors’ decisions to invest in Indonesia.